2018
DOI: 10.1007/s10566-018-9441-6
|View full text |Cite
|
Sign up to set email alerts
|

Linking Mother–Child Discrepancies to Behavioral Observations of Children’s Anxiety

Abstract: Background Informant discrepancies between mother and child have challenged the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
2
0
2
Order By: Relevance
“…Parent report on the SCARED-P for youths with depression only did not exceed the clinical cut off however, suggesting that anxiety symptoms may have been more internally experienced by these youths and/or that depression was the predominant overt issue impairing functioning. There was some consistent discrepancy between youth and parent reports on the SCARED, which is common in self-report measures, including on the SCARED (Sequeira et al, 2019 ; van Doorn et al, 2018 ), though it did not fall outside the margin of error for the present sample. The frequency of youth and parent reported anxiety symptoms across all diagnostic categories underscores the utility of providing anxiety focused interventions and varied assessments for youths and parents in this setting.…”
Section: Youth and Parent Reports Of Anxiety And Depressionmentioning
confidence: 47%
“…Parent report on the SCARED-P for youths with depression only did not exceed the clinical cut off however, suggesting that anxiety symptoms may have been more internally experienced by these youths and/or that depression was the predominant overt issue impairing functioning. There was some consistent discrepancy between youth and parent reports on the SCARED, which is common in self-report measures, including on the SCARED (Sequeira et al, 2019 ; van Doorn et al, 2018 ), though it did not fall outside the margin of error for the present sample. The frequency of youth and parent reported anxiety symptoms across all diagnostic categories underscores the utility of providing anxiety focused interventions and varied assessments for youths and parents in this setting.…”
Section: Youth and Parent Reports Of Anxiety And Depressionmentioning
confidence: 47%
“…No obstante, la literatura indica que la variabilidad encontrada habitualmente entre distintos informantes puede deberse: al efecto del método de recogida de información (i.e. autoinformado vs. heteroinformado) (Neyer, 2006), a la accesibilidad a la información que cada fuente informante tiene según la naturaleza interna-privada versus externa-manifiesta del contenido a evaluar (Johnston y Murray, 2003;van Doorn et al, 2018), al mejor despliegue de ciertas conductas en unos contextos y no en otros (Achenbach et al, 2017;, a la concepción de cada informante sobre lo que constituye un comportamiento normal (Richters, 1992), al propio estado emocional del informante (Berg-Nielsen, Vika y Dahl, 2003) y/o a la diferencia en la percepción de las prácticas parentales o las relaciones entre padres/madres e hijos/as (Hoeve et al, 2009). La tendencia incrementada del valor absoluto de las correlaciones entre rechazo parental y desajuste psicológico que se ha hallado en este estudio es esperable, en parte, por el posible efecto sinérgico del ambiente familiar global de no-afecto y el rechazo parental, lo que además es congruente con estudios previos (Germán et al, 2013;Glicklich, 2014;McKee et al, 2007).…”
Section: Discussionunclassified
“…No tenemos una explicación sobre las diferencias en estos patrones específicos de relaciones y solo nos queda constatarlas. Si bien, las relaciones significativas encontradas exclusivamente entre rechazo parental y los problemas interiorizados cuando es el menor quien informa del ajuste, está en consonancia con aquellas investigaciones (Johnston y Murray, 2003;van Doorn et al, 2018) que justifican estos resultados por la naturaleza interna y privada de los problemas interiorizados, a los cuales los menores tienen el mejor acceso. Son también consistentes con los estudios que los ha mostrado a los menores como los mejores informantes frente a los padres y madres cuando se pretende predecir el desajuste a partir del rechazo parental (Izquierdo-Sotorrío et al, 2016).…”
Section: Discussionunclassified
“…Furthermore, some studies revealed contradicting results for their anxiety disorders, such that parents showed somewhat higher agreement with their sons (Rapee et al, 1994). In contrast there was a higher agreement between mothers and their daughters (van Doorn et al, 2018). Other studies showed that parent-son agreement was significantly more substantial regarding behavioral disorders (Reich et al, 1982) and depressive symptoms (Angold et al, 1987).…”
Section: Moderators Of Mother-child Agreement On Child Outcomes: Chil...mentioning
confidence: 98%